CHANGES OF IMMUNE INDEXES DURING SUBLINGUAL ALLERGEN-SPECIFIC IMMUNOTHERAPY IN CHILDREN WITH HAY FEVER - I. M. Gaiduk; D. S. Korostovtsev; N. L. Shaporova; D. V. Breykin; O. V. Trusova; I. A. Kamaeva (Медицинская иммунология, 2014)
Aims of study: evaluation of immunological parameters in course of sublingual allergen-specific immunotherapy with tree pollen mixture in children with hay fever.Materials and methods: the study included one-hundred patients 5 to 18 years of age with hay fever (pollen rhinitis, rhinoconjunctivitis and/or asthma). Allergen-specific immunotherapy was administered pre-seasonally for three consecutive years. Cytokinechanges were studied in blood serum and in lavages from nasal cavity. Samples assessed before treatment and after 2nd and 3rd courses SLIT completion.Results: increased serum concentrations of IL-10, IFNγ, and decreased IL-4 contents were revealed in the course of treatment. No significant changes in cytokineconcentrations were detectable in nasal lavages.Conclusions: the changes revealed correspond to a shift of T cell response profile towards Th1 pathway, thus confirming pathogenetic effects of sublingual allergen-specific